2016
DOI: 10.18632/oncotarget.11898
|View full text |Cite
|
Sign up to set email alerts
|

SMYD3-mediated lysine methylation in the PH domain is critical for activation of AKT1

Abstract: AKT1 is a cytosolic serine/threonine kinase that is overexpressed in various types of cancer and has a central role in human tumorigenesis. Although it is known that AKT1 is post-translationally modified in various ways including phosphorylation and ubiquitination, methylation has not been reported so far. Here we demonstrate that the protein lysine methyltransferase SMYD3 methylates lysine 14 in the PH domain of AKT1 both in vitro and in vivo. Lysine 14-substituted AKT1 shows significantly lower levels of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 58 publications
(66 reference statements)
4
32
0
Order By: Relevance
“…We and others have reported the important roles of dysregulation of non‐histone protein methylation in carcinogenic processes in various types of human cancer. For example, SMYD3‐mediated AKT methylation at lysine 14 plays pivotal roles in activation of the AKT signaling pathway in breast and colon cancers, and PRMT1‐mediated methylation at arginine 887 of INCENP promotes mitosis of lung and cervical cancers …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have reported the important roles of dysregulation of non‐histone protein methylation in carcinogenic processes in various types of human cancer. For example, SMYD3‐mediated AKT methylation at lysine 14 plays pivotal roles in activation of the AKT signaling pathway in breast and colon cancers, and PRMT1‐mediated methylation at arginine 887 of INCENP promotes mitosis of lung and cervical cancers …”
Section: Discussionmentioning
confidence: 99%
“…We and others have reported the important roles of dysregulation of non-histone protein methylation in carcinogenic processes in various types of human cancer. For example, SMYD3-mediated AKT methylation at lysine 14 plays pivotal roles in activation of the AKT signaling pathway in breast and colon cancers, (16) and PRMT1-mediated methylation at arginine 887 of INCENP promotes mitosis of lung and cervical cancers. (39) In the present study, we have shown that SMYD2-mediated methylation of lysine 1610 on the EML4-ALK fusion protein is likely to be critically important for autophosphorylation of some tyrosine residues and the oncogenic activity of the fused proteins.…”
Section: Discussionmentioning
confidence: 99%
“…VEGFR1 methylation by SMYD3 augments VEGRF1 kinase activity, which is thought to enhance carcinogenesis [12]. Methylation of AKT1 at lysine 14 is essential for AKT1 activation [13]. In addition, SMYD3 was found to promote formation of inducible regulatory T cells and may be involved in reducing autoimmunity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For N‐ and C‐terminally EGFP‐tagged Akt1, FLIM showed no variations of fluorescence lifetimes within cells; thus indicating that methylation had no influence on the cellular localization of Akt1. Its methylation sites have been reported to be at Lys14, Lys 30, and Lys39 . Hence, we hoped to observe different FRET efficiencies for EGFP‐Akt1 and Akt1‐EGFP.…”
Section: Resultsmentioning
confidence: 99%